Skin sodium measured with 23Na MRI at 7.0 T. (18th October 2014) - Linz, Peter; Santoro, Davide; Renz, Wolfgang; Rieger, Jan; Ruehle, Anjuli; Ruff, Jan; Deimling, Michael; Rakova, Natalia; Muller, Dominik N.; Luft, Friedrich C.; Titze, Jens; Niendorf, Thoralf
<x xml:space="preserve">Abstract</x> Skin sodium (Na+) storage, as a physiologically important regulatory mechanism for blood pressure, volume regulation and, indeed, survival, has recently been rediscovered. This has prompted the development of MRI methods to assess Na+ storage in humans (23Na MRI) at 3.0 T. This work examines the feasibility of high in‐plane spatial resolution 23Na MRI in skin at 7.0 T. A two‐channel transceiver radiofrequency (RF) coil array tailored for skin MRI at 7.0 T (f = 78.5 MHz) is proposed. Specific absorption rate (SAR) simulations and a thorough assessment of RF power deposition were performed to meet the safety requirements. Human skin was examined in an in vivo feasibility study using two‐dimensional gradient echo imaging. Normal male adult volunteers (n = 17; mean ± standard deviation, 46 ± 18 years; range, 20–79 years) were investigated. Transverse slices of the calf were imaged with 23Na MRI using a high in‐plane resolution of 0.9 × 0.9 mm2. Skin Na+ content was determined using external agarose standards covering a physiological range of Na+ concentrations. To assess the intra‐subject reproducibility, each volunteer was examined three to five times with each session including a 5‐min walk and repositioning/preparation of the subject. The age dependence of skin Na+ content was investigated. The 23Na RF coil provides improved sensitivity within a range of 1 cm from its surface versus a volume RF coil which facilitates high in‐plane spatial resolution imaging of human skin. Intra‐subject variability of human skin Na+ content in the volunteer population was <10.3%. An age‐dependent increase in skin Na+ content was observed (r = 0.78). The assignment of Na+ stores with 23Na MRI techniques could be improved at 7.0 T compared with current 3.0 T technology. The benefits of such improvements may have the potential to aid basic research and clinical applications designed to unlock questions regarding the Na+ balance and Na+ storage function of skin. Copyright © 2014 John Wiley & Sons, Ltd.